Oxygen consumption of the amphibious snail Pomacea lineata; Influence of weight, sex and environments - Santos, Cristina Amabile Zavaglia Dos [UNESP]; Mendes, Erasmo Garcia [UNESP] (Elsevier, 1981)
1. 1. Under normoxic conditions at 25°C Pomacea lineata, free to move into or out of water, showed an increase in O2 consumption with increase in body size (dry wt), the slope of the log-log plot of these two parameters being b = 0.76. 2. 2. The metabolic rate decreased with weight. 3. 3. Males and females in a sexually receptive state did not exhibit significantly different QO2 values. 4. 4. The metabolic rates of animals when under water using ctenidium did not differ significantly from when out of water using the lung. © 1981.